Method for synthesizing organic iodide, composition for forming perovskite containing organic iodide, and photovoltaic cell having perovskite layer obtained therefrom
The in-situ synthesis of hydrogen iodide reacts with organic cations to generate high-purity iodide salts, which are used for perovskite synthesis, solves the problem of low purity of perovskite precursors and improves the quality of the perovskite layer and the performance of photovoltaic cells.
Patent Information
- Application Number
- CN202080026905.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-06-01
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2040-06-01
AI Technical Summary
In the prior art, it is difficult to obtain high-purity iodides when preparing perovskite precursors, which affects the quality of perovskite films and the performance of photovoltaic cells.
By synthesizing hydrogen iodide in situ, reacting organic cations with molecular iodine in a solvent medium, a salt with general formula RxNI is generated, and applied to the perovskite formation composition as a substrate for perovskite synthesis .
The purity of perovskite precursors and the quality of perovskite layers are improved, the performance and stability of photovoltaic cells are improved, and production costs are reduced.
Smart Images

Figure CN114096511B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for obtaining a x The invention relates to a method for preparing a salt of organic iodide (NI), characterized in that the obtained product has high purity, a composition for perovskite formation, which is suitable for obtaining a perovskite photosensitive coating and comprises at least one iodide obtained using the method, and a photovoltaic cell having a perovskite photosensitive layer formed using the composition. Background Art
[0002] Photosensitive coatings are used in the production of photovoltaic cells, i.e. semiconductor components for converting solar radiation into electrical energy. In photovoltaic cells, the photoactive layer acts as a sunlight (photon) absorber, so it is usually used as the visible surface of the cell and is coated with a suitable sunlight-permeable (semi-transparent / transparent) electrode material.
[0003] One known type of photosensitive coating is photosensitive ink. One of the advantages of photosensitive ink is that the ink is applied to the substrate in a simple and inexpensive manner, i.e. the ink is printed on, wherein the choice of printing technique depends on the scale of production, the type of substrate and the physical properties of the ink, such as its viscosity and adhesive properties.
[0004] Known organic photosensitive inks contain organic film-forming substances in the form of doped polymers or monomers which are capable of polymerizing after application to a target substrate.
[0005] For example, US patent application US20130087744 describes a method comprising a B A photovoltaic ink composition composed of a polymeric precursor of (ER)3, wherein M B is a metal selected from In, Ga or Al; E is S or Se, and R represents an alkyl, aryl, heteroaryl, alkenyl, amide or silyl moiety. Organic substances such as aliphatic and aromatic hydrocarbons as well as siloxanes, cyclosiloxanes, silicone fluids, acetonitrile, esters and ethers are used as ink solvents. The ink has a molecular formula M alk M B (ER)4 or a compound having the molecular formula M alk (ER) a mixture of compounds, wherein M alk is Li, Na or K, and R is an alkyl or aryl moiety. Other ink ingredients are surfactants, dispersants and emulsifiers, defoamers, viscosity modifiers, antioxidants and pro-adhesive agents. Depending on the composition, the ink is in the form of a suspension or solution, prepared by mixing all the ingredients. The ink is used as a photovoltaic layer and is applied to the substrate by printing. To cure the applied coating, the ink is dried by evaporation of the solvent.
[0006] Furthermore, perovskites are known materials for obtaining photovoltaic cells. Perovskites are hybrid organic-inorganic compounds with the general formula ABX3, where, typically in solar cells, A is an organic methylammonium cation (CH3NH3 + ), whose presence enhances the solubility of the material, making the perovskite suitable for thin-layer applications. B is an inorganic cation such as a lead cation (Pb 2+ ), and the anion X is selected from a halogen group, usually iodide (I - ), bromide (Br - ) or chloride (Cl - ) anions. Perovskites are produced in the form of films, i.e. thin coatings, which constitute the photoactive layer of photovoltaic cells, wherein in a cell with a standard architecture the perovskite layer is located between layers of p-type and n-type conducting material, which are usually covered with suitable electrodes, including one that allows the transmission of sunlight photons.
[0007] Perovskite films used in the photoactive layer of photovoltaic cells are prepared from a perovskite-forming composition, which is a colloidal solution containing a perovskite precursor, i.e., a substrate for synthesizing a specific perovskite, constituting a dispersed phase, wherein the colloid contains a suitable liquid as a dispersion medium, usually an organic solvent.
[0008] Also known are two-component perovskite-forming compositions which comprise two physically separate components which react to form the perovskite after mixing.
[0009] In the perovskite-forming composition constituting the colloidal solution, the colloidal particles are in the form of a complex, typically represented by a structure of polyhalide lead in organic and inorganic components, which can be adjusted by changing the coordination degree of the complex, thereby allowing the formation of a perovskite layer in the form of a thin film with predetermined film coverage parameters and the morphology of the obtained perovskite structure.
[0010] Also known are perovskite-forming compositions in the form of inks containing at least one perovskite precursor, wherein the curing mechanism (ie the formation of a photosensitive coating) comprises the synthesis of a perovskite from the perovskite precursor contained in the composition.
[0011] International patent application WO2016088019 discloses a film-forming composition comprising at least two perovskite precursors (e.g., CH3NH3I and PbI2 or NH2CH=NH2I and PbI2 or CsI and SnI2). The composition may be in the form of a powder or ink and may include dimethylformamide (DMF) or isopropyl alcohol (IPA) as a solvent and additives including thickeners such as glycerol or d-sorbitol and a crystallization retardant such as dimethyl sulfoxide (DMSO). The method of curing the composition on a selected substrate to form a photosensitive layer comprises applying a layer of the composition having an appropriate thickness to a substrate and curing the composition, wherein the curing comprises synthesizing a suitable perovskite from a perovskite precursor and evaporating the solvent if the solvent is present in the composition. According to WO2016088019, depending on the form and composition of the film-forming composition, the film-forming composition can be applied to the substrate using spin coating techniques, printing and heating to apply the layer or applying the coating from the gas phase, including dual source evaporation, or using ablation techniques, or printing (especially including inkjet printing), as well as spraying, blade coating, meniscus coating, slit die coating or dip coating. The resulting photosensitive layer is characterized by having good photon absorption, and the prepared photovoltaic cell containing the perovskite thin film obtained by curing the film-forming composition exhibits good efficiency.
[0012] In addition, the scientific publication "Unraveling the hidden function of astabilizer in a precursor in improving hybrid perovskite film morphology for high efficiency solar cells" by Zhengguo Xiao et al., Energy & Environmental Science, DOI: 10.1039 / c6ee00183a, published on January 28, 2016, describes the synthesis of organometallic alkyl halides "OPT" (organometallic trihalide perovskites) containing three corresponding halogen atoms. The publication describes the role of phosphoric acid (I) also known as phosphinic acid H3PO2 in stabilizing hydrogen iodide HI, which is necessary for the synthesis of perovskite precursors from the OPT group - methylammonium iodide (MAI-methylammonium iodide). In fact, the presence of phosphoric acid (I) H3PO2 as a stabilizer for hydrogen iodide HI during the synthesis of MAI affects the contamination of the reaction product with methylammonium hypophosphite MAH2PO2, which results from the reaction of H3PO2 with methylamine (MA). Said contamination leads to a substantial reduction in the crystallization reaction rate, that is, the synthesis of perovskites from MAI contaminated with MAH2PO2 and PbI2 (lead iodide) leads to the formation of highly uniform and smooth perovskite layers with large grains, due to the formation of the intermediate phase Pb(H2PO2)2. The synthesis of perovskites using MAI purified with MAH2PO2 by recrystallization, in turn, produces coarse-grained heterogeneous perovskite films, indicating that the contamination with MAH2PO2 promotes the synthesis of perovskites. The authors of the publication suggest the use of Pb(H2PO2)2 as nucleation centers for perovskite crystals.
[0013] Wei Zhang et al., “Enhanced optoelectronic quality of perovskite thin films with hypophosphorous acid for planar heterojunction solar cells,” NATURE COMMUNICATIONS, DOI: 10.1038 / ncomms10030, published on November 30, 2015, describes perovskite semiconductors such as CH3NH3PbI3. The authors of the publication note that the addition of phosphoric acid (I) (HPA) to the perovskite precursor solution reduces the oxidized I2 (molecular iodine) to I- (iodide anion), thus significantly improving the quality of the perovskite film obtained. This improves the stoichiometry of the perovskite crystals obtained.
[0014] Another scientific publication, “Ultrasmooth organic–inorganic perovskite thin-film formation and crystallization for efficient planar heterojunction solar cells” by Wei Zhang et al., NATURE COMMUNICATIONS, DOI: 10.1038 / ncomms7142, published on February 30, 2015, describes the role of anions in perovskite synthesis in solution and how they affect the growth of perovskite crystals, which in turn affects the production and quality of perovskite films. The authors of this publication used lead acetate (Pb(OAc)2) instead of the traditionally used lead chloride or lead iodide (PbCl2, PbI2), which resulted in faster growth of perovskite crystals and a smoother surface of the perovskite film. Moreover, the heating time is shorter during the preparation of perovskite CH3NH3PbI3 using precursors Pb(OAc)2 and MAI, which helps to remove excess CH3NH3OAc from the mixture.
[0015] According to the above publications, not only the concentration of the perovskite precursor in the perovskite-forming composition, but also all the above methods for preparing and purifying the perovskite precursor of the perovskite-forming composition in the form of a colloidal solution substantially affect the quality and morphology of the perovskite thin film crystals obtained using a specific composition.
[0016] Therefore, methods for obtaining perovskite precursors, i.e., raw materials for synthesizing perovskites, are constantly being improved to obtain compounds with appropriate purity so that these compounds can be used to prepare perovskite-forming compositions to form fine perovskite coatings showing appropriate morphology and crystal quality, so that photovoltaic cells produced using such coatings as photosensitive elements have increasingly superior performance.
[0017] Therefore, it would be advantageous to develop a method for synthesizing perovskite precursors and perovskite compositions comprising the same, which would enable the preparation of perovskite coatings showing improved morphology and quality of the perovskite crystals. Summary of the invention
[0018] Disclosed is a method for obtaining a x The method of preparing a salt of NI, wherein R x N is an organic cation (R xN + ), R represents a substituent (R-), independently selected from organic substituents R 1 -、R 2 -、R 3 - and hydrogen (H-), x is a group consisting of an organic cation R x N + The number of substituents R-directly connected to the nitrogen (N) atom in the - The method comprises: preparing a reaction mixture, comprising the following steps: in situ synthesizing hydrogen iodide (HI) by mixing molecular iodine (I2) and formic acid (HCOOH) in a solvent medium at a molar ratio of molecular iodine (I2): formic acid (HCOOH) of not less than 1.01:1, and in a solvent medium to provide an organic cation R x N + Donor: Molecular iodine (I2) is introduced as an organic cation R in a molar ratio of not less than 1.01:1 x N + The reaction mixture is kept at a temperature of not less than 20°C for a desired time to obtain a compound having the general formula R x The reaction product of NI salt.
[0019] Preferably, the organic cation R x N + The donor comprises as an organic substituent R a moiety independently selected from the group consisting of linear or branched alkyl substituents 1 -、R 2 - and optionally R 3 -, and the substituent molecule of the alkyl substituent contains 1 to 8 carbon atoms, and optionally contains at least one heteroatom replacing a carbon atom or a hydrogen atom in the substituent molecule, wherein the heteroatom is selected from the group consisting of silicon, oxygen, nitrogen, sulfur, iodine, chlorine and bromine.
[0020] Preferably, molecular iodine (I2) and formic acid (HCOOH) are mixed in a molar ratio of molecular iodine (I2):formic acid (HCOOH) of 1.01:1 to 1.1:1, and to provide an organic cation R x N + The organic cation R is reacted in an amount of 1.01:1 to 1.50:1 in a molar ratio of donor: molecular iodine (I2). x N + The donor is introduced into a solvent medium.
[0021] Preferably, molecular iodine (I2) and formic acid (HCOOH) are mixed in a molar ratio of iodine (I2):formic acid (HCOOH) of 1.01:1.
[0022] Preferably, the reaction mixture is heated to a temperature in the range of 20 to 80°C.
[0023] Preferably, after the in situ synthesis of hydrogen iodide (HI), the organic cation R x N + The donor is introduced into a solvent medium.
[0024] Preferably, an amine is used as the organic cation R x N + donor, and the obtained salt (R x NI) comprises an organic cation (R) selected from the group consisting of x N + ): Alkyl ammonium cation (R(H3)N + ), dialkylammonium cation R2(H2)N + and trialkylammonium cations (R3(H)N + ).
[0025] Preferably, a primary alkylamine of the general formula RNH2 is used as the organic cation R x N + donor, and the resulting salt, ie, alkylammonium iodide, has the general formula R(H3)NI, wherein the substituent R represents an alkyl moiety containing 1 to 8 carbon atoms.
[0026] Preferably, methylamine is used as the organic cation R x N + donor, and methylammonium iodide (MAI) was obtained as a salt.
[0027] Preferably, octylamine is used as the organic cation R x N + donor, and octylammonium iodide (OAI) was obtained as a salt.
[0028] Preferably, an amidine salt is used as the organic cation R x N + donor and obtain amidine iodide as a salt (R2N-(R 3 )C=N(H2)I).
[0029] Preferably, formamidine acetate is used as the organic cation R x N + donor and obtain formamidine iodide (FAI) (H2N-C(H)=N(H2)I) as a salt.
[0030] Preferably, the solvent medium comprises at least one compound selected from the group consisting of methanol, ethanol, anhydrous ethanol, isopropanol, diisopropyl alcohol, oxane, tetrahydrofuran (THF) and dimethylformamide (DMF).
[0031] Preferably, the solvent medium is water.
[0032] Preferably, preparing the reaction mixture further comprises the step of introducing a catalyst into the solvent medium, wherein the catalyst has the general formula R x NI of salt.
[0033] Preferably, the catalyst is a salt R x NI same compound.
[0034] Preferably, the catalyst is obtained by a process according to the present disclosure.
[0035] Preferably, the catalyst is introduced in a molar ratio of catalyst:molecular iodine (I2) ranging from 0.01:1 to 0.03:1.
[0036] In addition, a compound having the general formula R prepared using the method according to the present disclosure is disclosed. x Use of NI salts as substrates in perovskite synthesis.
[0037] In addition, a perovskite-forming composition is disclosed, which comprises a perovskite-forming composition having a general formula R obtained by the method according to the present disclosure. x NI of salt.
[0038] Preferably, the composition comprises a compound having the general formula R selected from the group consisting of x Salts of NI: methylammonium iodide (MAI), ethylammonium iodide, propylammonium iodide, butylammonium iodide, pentylammonium iodide, hexylammonium iodide, heptylammonium iodide, octylammonium iodide (OAI) and formamidine iodide (FAI).
[0039] Preferably, the composition further comprises at least one lead salt and at least one solvent.
[0040] Preferably, the composition further comprises methyl dihydrogen phosphate ammonium (I) CH3NH3H2PO2.
[0041] Preferably, the composition comprises the following compounds: methylammonium iodide (MAI), anhydrous lead (II) acetate (CH3COO)2Pb and lead (II) chloride PbCl2, in amounts effective for the synthesis of perovskite from said compounds, as well as dimethylformamide (DMF) as a solvent and methylammonium dihydrogen phosphate (I) CH3NH3H2PO2 in an amount of 0.3% relative to the weight of methylammonium iodide (MAI) contained in the composition.
[0042] Preferably, the composition comprises formamidine iodide (FAI), methylammonium bromide CH3NH3Br, lead (II) iodide PbI2 and cesium iodide (CsI) in amounts effective for synthesizing perovskite from said compounds.
[0043] Also disclosed is a photovoltaic cell comprising: x A perovskite layer prepared from a salt of NI, the salt being obtained using the method according to the present disclosure.
[0044] Preferably, the cell comprises a perovskite layer obtained from a perovskite-forming composition comprising the ingredients as described above. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] The object of the invention is illustrated in an exemplary embodiment in the accompanying drawings, in which:
[0046] Figure 1A and Figure 1B To prepare an organic iodide (R x NI) Schematic diagram of the synthesis reaction;
[0047] Figure 2A and Figure 2B Schematic diagram of the synthesis reaction of methylammonium iodide (MAI) using the method according to the present disclosure;
[0048] Figure 3A and Figure 3B Schematic diagram of the synthesis reaction of octylammonium iodide (OAI) using the method according to the present disclosure;
[0049] Figure 4A and Figure 4B Schematic diagram of the synthesis reaction of formamidine iodide (FAI) using the method according to the present disclosure;
[0050] Figure 5 are schematic diagrams of structural formulas and semi-structural formulas of exemplary organic iodides obtained using the methods according to the present disclosure;
[0051] Figure 6 Shows an example of synthesizing perovskites from iodides obtained using methods according to the present disclosure;
[0052] Fig. 7A , Figure 7B and Figure 7C SEM image showing the perovskite coating in thin film form on PEDOT / PET / ITO substrate;
[0053] Fig. 8A Shows the synthetic X-ray diffraction pattern of CH3NH3PbI3 obtained by using MAI synthesized by the method of the present invention, using MAI synthesized by the method of the present invention and adding MAH2PO2, Figure 8B The enlarged peak corresponding to the (110) reflection in the tetragonal plane of the perovskite phase is shown with Fig. 8A For comparison, Figure 8C The enlarged peak corresponding to the PET material is shown (control);
[0054] Fig. 9A Measurement results showing that the cell efficiency (η), which determines the energy conversion efficiency of the cell, depends on the type of perovskite-forming composition used to form the perovskite layer of the cell;
[0055] Fig. 9B Shows test results presenting the current density-voltage dependence of selected perovskite cells;
[0056] Fig.10 Shows the results of aging tests on selected cells: aging at maximum power point under 0.8 sun, in an inert atmosphere and at a temperature of 32°C;
[0057] Fig.11A SEM images of perovskite coatings prepared using Composition I and Example VIII are shown. Fig. 11B SEM images showing the perovskite coating prepared using Composition II and Example VIII;
[0058] Fig. 12A The synthetic X-ray diffraction patterns of the two perovskite networks; Fig. 12B It is the amplified peak corresponding to the tetragonal plane reflection (100) of the perovskite phase;
[0059] Fig.13 The current density-voltage dependence of the prepared cells is shown;
[0060] Fig.14A A picture showing a colloid containing MAI obtained using the method according to the present invention;
[0061] Fig. 14B Pictures showing colloids of the same composition containing MAI obtained using the prior art method (commercially available MAI);
[0062] Fig. 14C Photographs showing a colloid of the same composition containing MAI obtained using the prior art method and recrystallized once;
[0063] Fig.14D Photographs showing a colloid of the same composition containing MAI obtained using a prior art method and recrystallized three times. DETAILED DESCRIPTION
[0064] The method developed according to the invention allows the preparation of compounds useful as perovskite precursors, which are compounds having the general formula R x The salt of N has the ionic symbol RxN + I - , where R x N + is an organic cation, I -is an iodide anion, x is the number of substituents directly bonded to the nitrogen atom, preferably x is 3 to 4 (if x=3, the double bond in the organic cation exists between a carbon atom in one R portion and a nitrogen atom).
[0065] The developed preparation R x The method of NI compounds ensures improved purity of the resulting products, which in turn enables their use as perovskite precursors in various perovskite-forming compositions, including colloidal solutions, such as inks, for the production of perovskite coatings with improved morphology and quality of perovskite crystals.
[0066] The developed iodide synthesis method differs from the prior art methods in that the method according to the present disclosure involves Steps for obtaining hydrogen iodide (HI) in situ in a reaction medium In other words, according to the developed method, hydrogen iodide (HI) is not used as a direct substrate for the synthesis of the respective iodide. Instead, the developed method comprises a step of supplying a substrate suitable for the in situ hydrogen iodide (HI) synthesis into the reaction medium.
[0067] The developed method allows to obtain as a x Various compounds of iodide salts of NI, wherein the organic cation R x N + Selected from the group consisting of:
[0068] - having the general formula R4N + (x=4) ammonium cations, including alkylammonium cations R 1 (H3)N + , dialkylammonium cation R 1 R 2 (H2)N + and trialkylammonium cation R 1 R 2 R 3 (H)N + ,and
[0069] - having the general formula R3N + (x=3) ammonium cations, including amidine cations R 1 R 2 N-(R 3 )C=N(H2) + and formamidinium cation R 1 R 2 NC(H)=N(H2) + ,
[0070] According to the general formula of the above cation, part R- is selected from the group consisting of H-, R 1 -、R 2 - and R 3 -. Substituents R-, R 1 -、R2 -、R 3 - may be the same or different moieties, selected from the group consisting of: hydrogen (H-), straight-chain and / or branched aliphatic hydrocarbons (C y H z -), including saturated hydrocarbons and / or alicyclic hydrocarbons containing one or more unsaturated bonds and aromatic hydrocarbons. Preferably, the organic cation (R x N + ) each substituent R-(R 1 -、R 2 -、R 3 -) may contain 1 to 8 carbon atoms in the molecule, i.e. for at least one substituent R-(R 1 -、R 2 -、R 3 -) has the general formula C y H z -, y may be 1÷8. In addition, at least one substituent R of the organic cation 1 -、R 2 -、R 3 - may have at least one carbon atom or hydrogen atom replaced by another atom, for example: silicon, oxygen, nitrogen, sulfur, iodine, chlorine or bromine.
[0071] For example, the developed method can be used to obtain iodized salt (R x NI), where the organic cation (R x N + ) When x=4, it is methylammonium CH3(H3)N + Cation, ethylammonium CH3CH2(H3)N + Cation, Propylammonium C3H7(H3)N + Cation, Butylammonium C4H9(H3)N + Cation, amyl ammonium H3C5H 11 N + Cation, hexyl ammonium H3C6H 13 N + Cation, Heptylammonium C7H 15 (H3)N + Cation or Octyl ammonium C8H 17 (H3)N + The cation, when x=3, is formamidine (H2N-HC=NH2) + Cation or guanidine (H2N)2-C=NH2) + cation.
[0072] For greater clarity, examples of iodide salts obtained using the method of the present invention are shown in the form of structural formulas and semi-structural formulas. Figure 5In which Formulas I and II are general iodide formulas, Formula I represents a salt having the general formula R4NI (i.e., x=4), Formula II represents a salt R3NI (i.e., x=3), Formulas III, IV, and V respectively provide detailed examples of compounds obtained using the developed method, wherein Formula III represents methylammonium iodide (MAI), Formula IV represents octylammonium iodide (OAI), and Formula V represents formamidine iodide (FAI).
[0073] Therefore, the developed method enables to obtain the iodine salt R4NI ( Figure 5 , Formula I), such as methylammonium iodide (MAI), dimethylammonium iodide, propylammonium iodide, methylethylammonium iodide, butylammonium iodide, pentylammonium iodide, hexylammonium iodide, heptylammonium iodide, octylammonium iodide (OAI), and compounds having the general formula R3NI( Figure 5 , an iodide salt of formula II), such as formamidine iodide (FAI) or guanidine iodide (GAI).
[0074] Figure 1A , Figure 1B , Figure 2A , Figure 2B , Figure 3A , Figure 3B , Figure 4A , Figure 4B is a schematic diagram of the reactions occurring during the synthesis according to the developed method, Figure 1A , 2A , 3A and 4A show the synthesis without using a catalyst, while Figure 1B , 2B , 3B and 4B show the synthesis using a catalyst, which is an option. x NI) method comprises the following steps:
[0075] - supplying molecular iodine I2 to the reaction medium in excess relative to formic acid (HCOOH) and relative to the organic cation (R x N + ) Donor shortage,
[0076] - formic acid (HCOOH) is provided in the above-mentioned amount relative to molecular iodine (I2) to produce hydrogen iodide (HI) in situ (in the reaction medium), with the release of carbon dioxide (CO2) as a by-product of the HI synthesis, and
[0077] - will act as an organic cation R x N + The donor compound is supplied to the reaction medium in the amounts indicated above, thus corresponding to the amount of molecular iodine (I2), and
[0078] -Organic cation R x N +The donor reacts with hydrogen iodide (HI) synthesized in situ in the reaction medium to produce the corresponding R x NI salt.
[0079] Depending on the target synthetic product, various organic compounds can be used as the organic cation R x N + donor, i.e., capable of dissociating in the reaction medium to form the corresponding organic cation R x N + (ie, selected from the group R4N + and R3N + cation) compounds.
[0080] Preferably, compounds are used as organic cations R, the dissociation of which does not involve the introduction of additional and difficult-to-remove contaminants into the reaction medium. x N + Donor.
[0081] According to the developed preparation R x NI salt method, used as organic cation R x N + Examples of donor compounds:
[0082] For example, amines, preferably primary amines, preferably containing 1 to 8 carbon atoms in the molecule, such as methylamine (CH3NH2) to obtain methylammonium iodide (CH3NH3I), ethylamine (C2H5NH2) to obtain ethylammonium iodide (C2H5NH3I) or octylamine (C8H 17 NH2) to obtain octyl ammonium iodide (C8H 17 NH3I), can be used as organic cation R4N + (ie x = 4) donor. The corresponding amine will thus dissociate to produce the corresponding organic cation R4N which is the substrate for salt synthesis + .
[0083] In addition, acetic acid amidines, such as formamidine acetate, can be used as organic cation R3N + (i.e. x = 3) Donor: (Formula in ion symbol: [(HC(NH2)2] + [CH3COO] - ), because these compounds are easily dissolved and dissociated into their respective organic cations R3N under the reaction conditions. + and acetate anions, which are converted into acetic acid during the reaction and can be easily removed from the reacted mixture by evaporating from the solution due to its low boiling point.
[0084] The above compounds selected as organic cation donors provide high purity synthetic products, i.e., salts containing iodide anions and organic cations, thereby making the salts prepared by using the developed method R x NI The quality of the resulting perovskite coatings was improved.
[0085] According to the organic cation Rx N + Solubility of the donor. The reaction can be carried out in polar or nonpolar media. Various solvents provide good solubility of molecular iodine (I2) (reactions shown in Figures 1A, 2A, 3A, and 4A) or ionized iodine I3 - (Reactions shown in Figures 1B, 2B, 3B and 4B) and providing the organic cation R x N + Good solubility of the donor. In addition, the solvent should preferably allow the reaction to proceed at a temperature above 50° C., so that, for example, the solvent should have a boiling point of more than 50° C., and more preferably, a boiling point of 50 to 150° C. When cleaning the reaction product, a solvent having a boiling point above 150° C. is difficult to remove, and therefore, such a solvent may constitute undesirable contamination and is therefore less preferably used.
[0086] For example, in the embodiment of the present invention, methylamine is used as an organic cation donor, and the reaction can be carried out in water, methanol, ethanol, anhydrous ethanol (for example, 99.8% concentration, obtained by distillation with the addition of benzene; small amounts of benzene contamination of the solvent will not adversely affect the final purity of the product because it may be removed during the purification process), isopropanol, a mixture of a suitable alcohol and water, diisopropyl alcohol ... The reaction is preferably carried out in a solvent such as alkane, tetrahydrofuran (THF), etc., wherein the reaction is preferably carried out using anhydrous ethanol as a solvent because anhydrous ethanol provides a relatively high solubility of substrates including molecular iodine and organic cation donors including methylamine. In addition, the boiling point of ethanol is 78° C., thus allowing the reaction to be carried out at a preferred temperature of more than 50° C. In addition, anhydrous ethanol is easily removed during the purification process of the reaction product.
[0087] As the number of carbon atoms in the molecule of the organic cation donor increases, the polarity of the molecule decreases in favor of a nonpolar molecule. This requires the use of, for example, methanol, ethanol, isopropanol, anhydrous ethanol, diisopropyl alcohol, Solvents such as oxane and tetrahydrofuran (THF) were used instead of water.
[0088] For example, when octylamine or formamidine acetate is used as the organic cation donor, ethanol can be used as the solvent.
[0089] The introduction of the organic cation donor during the preparation of the reaction mixture is preferably carried out at a temperature in the range of 0 to 30° C. For example, the addition of the organic cation donor can be carried out at room temperature, since the reaction initiated by such addition is exothermic in nature. After the addition of the compound acting as an organic cation donor, the reaction mixture is preferably heated to a temperature exceeding 50° C. This ensures an increase in the reaction rate. Under such temperature conditions, the reaction can be carried out in a relatively short time, for example less than 2 hours, with a satisfactory product yield.
[0090] Figure 1A, 2A , 3A, 4A schematically represent the various reaction stages of the synthesis of iodide salts according to the developed method in the form of stoichiometric equations, wherein Figure 1A YesR x General representation of the NI iodide synthesis reaction, and Figure 2A represents the synthesis of methylammonium iodide (MAI), Figure 3A represents the synthesis of octylammonium iodide (OAI), and Figure 4A represents the synthesis of formamidine iodide (FAI). Figure 1A , 2A In , 3A, and 4A, the reactions labeled with reference numbers 1 and 2 represent individual synthetic steps, including intermediates, while the reaction labeled with reference number 3 is a summary of reactions 1 and 2.
[0091] like Figure 1A , Figure 2A , Figure 3A , Figure 4A As shown, in the first synthetic step (reaction 1), formic acid (HCOOH) reacts with molecular iodine (I2) to form hydrogen iodide (H + I - ) and the byproduct carbon dioxide (CO2) released. The hydrogen iodide formed constitutes the source of iodide anions. Then the iodide ion (I - ) reacts with a compound as an organic cation donor (reaction 2) to produce a reaction product, i.e., an iodide of the corresponding organic cation R x NI.
[0092] The reaction is carried out using an excess of iodine (I2) relative to formic acid (HCOOH), wherein, preferably, an excess of iodine in a molar ratio of 1.01 (I2): 1.0 (HCOOH) to 2.0 (I2): 1.0 (HCOOH) is used in the reaction, more preferably, molecular iodine (II2) is used in an excess in a molar ratio of 1.01 (I2): 1.0 (HCOOH) to 1.10 (I2): 1 (HCOOH) relative to formic acid, and the most preferred molar ratio is 1.05 (I2): 1 (HCOOH).
[0093] An excess of molecular iodine relative to formic acid in the reaction medium provides for the synthesis of the corresponding iodide salts with improved (excellent) purity.
[0094] Even if iodine (I2) is slightly excessive relative to formic acid (HCOOH), more preferably I2 is excessive relative to HCOOH within the above range, when its donor is added to the reaction mixture, the formation of formate ([R x N + ][HCOO - ]) by-product. This salt ([Rx N + ][HCOO - ]) is difficult to separate from the reaction products and, in some cases (particular salts and particular products), is impossible without expensive specialized purification methods. It is therefore advantageous to use a moderate excess of molecular iodine.
[0095] The use of an excess of molecular iodine relative to formic acid always results in the restriction of difficult-to-remove byproducts (R x N + ][HCOO - ]) to improve the purity of the obtained product, among which the most favorable molecular iodine excess makes it difficult to remove salts ([R x N + ][HCOO - ]) is significantly reduced to 1.01 to 1.10 mol I2 per 1 mol HCOOH.
[0096] Furthermore, in order to remove the iodine present in the mixture after the reaction, the product needs to be purified. If the excess amount of iodine used exceeds the prescribed amount, the purification step (recrystallization) may need to be repeated, which will incur additional costs due to the use of additional solvents, which is also time-consuming.
[0097] Therefore, in order to prevent the final product from being contaminated by excess unreacted iodine and reaction byproducts in the form of acetate ([R x N + ][HCOO - ]) contamination, a preferred excess of iodine can be used of 1.01 mol I2 per 1 mol HCOOH, such a value providing the best high purity of the final product.
[0098] In addition, the reaction is carried out in an excess of organic cation donor ( R x N + ) (the example of which is shown above), wherein the most preferred excess of the organic cation donor relative to molecular iodine (I2) is in the range of 1.01 to 1.50 moles of the organic cation donor per 1 mole of molecular iodine (I2). The use of an excess of the organic cation donor provides the following advantages. In particular, the excess of the organic cation donor relative to molecular iodine ( R x N + )Ensure complete reaction of the hydrogen iodide (HI) obtained in situ with the organic cation. If the obtained HI remains in the reaction environment, which is due to the molar deficiency of the organic cation donor at the end of the reaction, this remaining acid HI may be oxidized to iodine-containing oxyacids, such as HIO, HIO2, HIO3 and HIO4, which may form by-products (in the form of corresponding salts) through anion exchange reactions between the iodine-containing oxyacids and the reaction products. Such salts will be difficult to separate from the products, resulting in a lower purity of the product (corresponding iodine salt). Therefore, in order to prevent the in situ prepared hydrogen iodide (HI) from being excessive relative to the organic cation donor, an excess of the organic cation donor is used. (R x N + ) , which prevents contamination of the reaction products, as described above. In other words, the amount of organic cation in excess relative to the amount of molecular iodine (I2) added to the reaction medium (R x N + ) The purity of the obtained product is ensured. (R x N + ) According to the embodiments of the present disclosure, the unreacted excess of the donor in a gaseous or liquid state can be easily separated from the reaction product under given reaction conditions using generally known purification techniques.
[0099] In preparing the reaction mixture, an excess of organic cation (R x N + Another advantage of the iodine donor is that the prices of the above compounds (e.g. methylamine) are relatively low compared to the price of molecular iodine (I2), which means that the cost of preparing the corresponding iodides using the developed method is reduced.
[0100] Optionally, in order to achieve improved time efficiency, salt R x The synthesis reaction of NI can be carried out in the presence of a small amount of catalyst, wherein the catalyst is a compound, preferably, x The reaction using the corresponding catalyst is as follows Figure 1B As shown, as a general representation, as an exemplary embodiment, in Figure 2B The synthesis of methylammonium iodide (MAI) is shown in Figure 3B The synthesis of octyl ammonium iodide (OAI) is shown in Figure 4B The synthesis of formamidine iodide (FAI) is shown in FIG. 1 . Thus, for example, in order to obtain methylammonium iodide (MAI) as a product, a small (catalytic) amount of MAI is mixed with iodine (I2) in a first step, such as Figure 2B (Reaction 1) is shown.
[0101] Therefore, similar to the synthesis steps of the individual iodides MAI, OAI and FAI, no catalyst ( Figure 2A , 3A 、4A)、 Figure 2B , 3Band 4B, reactions 1 to 3 show the individual steps of the products synthesized using the catalyst, indicating transition states and intermediates, while reaction 4 is a summary of the substrates and products of reactions 1-3.
[0102] from Figure 1B , 2B As can be seen from 3B and 4B, in the first step (reaction 1), the catalyst of the corresponding iodide salt (preferably the same as the obtained iodide salt) reacts with iodine (I2) to produce a transition state, namely the triatomic iodide anion I3 - , and then react with formic acid (reaction 2) to produce the respective iodine salts, in situ hydrogen iodide (HI) and carbon dioxide. Then (reaction 3), the resulting I - Iodide anion and organic cation donor compound R x N + reaction, producing the corresponding R x NI, i.e., iodide salt as the reaction product.
[0103] I3 is formed by adding a catalyst to the reaction - The ions are characterized by greatly improved solubility in polar solvents and they react more easily with formic acid HCOOH to generate hydrogen iodide (HI) in situ than molecular iodine (I2), which is slightly less likely to react with formic acid and obtain hydrogen iodide (HI) in situ. Therefore, the addition of a catalyst (e.g. Figure 1B , Figure 2B , Figure 3B , Figure 4B can speed up the reaction process.
[0104] Since the transition form is the triatomic iodine anion I3 - The formation of has an accelerating effect and the reaction can therefore be carried out, for example, on an industrial or semi-technical scale in the presence of a catalyst, thereby increasing the productivity of the compound.
[0105] The addition of the catalyst reduces the reaction time by about 60 to 180 minutes. Thus, the average reaction time is 20 to 120 minutes when the catalyst is added, and 120 to 300 minutes when no catalyst is added.
[0106] Another advantage of using a catalyst that is the same compound as the reaction product is that the purity of the obtained product is improved, because the catalyst and the reaction product are the same compound, and therefore the catalyst does not contaminate the product. However, using an iodide salt of a catalyst that is a compound different from the synthetic product, preferably R x NI, will also increase the reaction rate.
[0107] Preferably, the catalyst is added to the system in an amount of 0.01 to 0.03 moles per mole of iodine (II2), i.e., 0.01 (moles of catalyst): 1 (moles of I2) to 0.03 (moles of catalyst): 1 (moles of I2). The reaction in the presence of the catalyst is carried out in a temperature range of 0 to 80°C.
[0108] Therefore, in MAI synthesis, MAI may be preferably used as a catalyst, in OAI synthesis, OAI may be preferably used as a catalyst, and in FAI synthesis, FAI may be preferably used as a catalyst.
[0109] The R obtained using the developed method x NI iodide salts are characterized by having higher product purity and are suitable for use, for example, as one of the precursor components of each perovskite in a perovskite-forming composition to prepare a perovskite photoactive layer in a photovoltaic cell. The perovskite-forming composition is, for example, a perovskite ink for printing on various substrates (e.g., ITO).
[0110] The R obtained by the method of the present invention x The use of NI iodide in perovskite-forming compositions, especially those used in photovoltaic devices in the photoactive layer, is particularly advantageous. This is because the R x NI iodide is used as one of the substrates in the perovskite synthesis, ensuring the formation of a perovskite layer with improved morphology, thereby improving the photoactivity of the resulting perovskite layer.
[0111] Preferably, the obtained product (R x NI) to separate them from the unreacted substrates used in the synthesis.
[0112] Figure 6 The iodide R prepared using the method according to the present disclosure is shown x NI exemplary reactions for synthesizing perovskites. The obtained perovskites are suitable for use as photoactive layers in photovoltaic cells. Reactions 1, 2, 3, 5 and 6 represent syntheses in which one of the precursors of the perovskite is methylammonium iodide (MAI) prepared using the developed method, and the other precursor is an iodide, bromide or lead (II) chloride or tin (I) iodide, respectively. Reaction 4 represents a synthesis in which one of the perovskite precursors is formamidine iodide (FAI) prepared using the method according to the present disclosure, and the other perovskite precursor is lead (II) iodide.
[0113] Therefore, the iodides prepared using the developed method can be used to obtain various perovskites for photoactive layers, including in particular those for photovoltaics.
[0114] The iodide obtained using the developed method is suitable as a precursor component of perovskite for use in perovskite-forming compositions (e.g., according to Figure 6 The invention relates to a method for preparing a perovskite-forming composition comprising a perovskite-forming composition in the form of a colloidal solution containing a corresponding lead salt as a precursor of another perovskite, such as a lead halide, such as lead (II) iodide, lead (II) chloride or lead (II) bromide.
[0115] Furthermore, in the course of further studies, the results of which are discussed below in an embodiment of the present invention, it was found that a particularly advantageous perovskite-forming composition in the form of a colloidal solution is a composition comprising an iodide salt obtained using the developed method, the addition of methylammonium dihydrogen phosphate (I) CH3NH3H2PO2 being particularly suitable, since the perovskite-forming layer obtained with such a composition provides improved parameters of the photovoltaic cell obtained therefrom.
[0116] Example
[0117] Example I - Synthesis of methylammonium iodide (MAI) using MAI as catalyst:
[0118] In a round bottom flask, a portion of the MAI catalyst was dissolved in ethanol and 0.01 mole of MAI was added per mole of I2 iodine to obtain a bright translucent solution. Then, the entire portion of dark brown I2 iodine was added to the resulting solution in one step to obtain a brown, opaque solution, which confirmed the presence of iodine (I2) in the solution. After 5 minutes, it dissolved, indicating the formation of I3 in the solution. -(Otherwise the I2 molecular iodine would dissolve at a much lower rate). Formic acid was then added to the resulting mixture in a single step at a molar ratio of 0.97:1.0 relative to the I2 iodine, and macroscopically, no changes were observed in the flask. A suitable organic cation donor, methylamine, was then added to the solution. The methylamine was slowly added dropwise to the solution so that there were a total of 2.6 moles of methylamine per mole of I2 iodine added to the solution. Upon the addition of methylamine, the formation of bubbles and foaming of the contents of the flask were observed, indicating that CO2 gas was released from the reaction mixture. During the reaction, a temperature increase was also observed, indicating that the reaction was exothermic. Bubble formation was only observed after the addition of methylamine, which can be explained by the fact that the use of in situ generated hydrogen iodide (HI) significantly accelerated the reaction. After the addition of methylamine was complete, the brown mixture was heated for 1 hour while maintaining the temperature of the mixture at 80°C, and then the reaction was terminated. After heating for 1 hour, the mixture changed from brown to light brown; however, the color of the mixture is not considered to be an indicator of the termination of the reaction because the iodine used is in excess relative to the formic acid, preventing the conversion of all iodine (I2) into hydrogen iodide (HI). The excess iodine added to the reaction prevents the formation of methylammonium formate as a by-product of the reaction. The resulting product is separated by evaporating the solvent from the reaction mixture to obtain a yellow and brown powder, which is completely dissolved in boiling anhydrous ethanol (100%) for recrystallization. After cooling to room temperature, ether is added to the mixture to precipitate more product. The precipitate is filtered and washed with ether until the precipitate becomes white. The resulting precipitate is the reaction product, i.e., MAI, which is dried in vacuo for 5 hours (pressure less than 0.2 mbar) and then the product is weighed. Compared with the theoretical yield according to the stoichiometry of the reaction, an 88% yield of the product (MAI) is obtained. The composition of the resulting product is analyzed to confirm the absence of even trace amounts of phosphonium salts because no phosphorus donor is used at any step of the synthesis.
[0119] The resulting product was also tested for the presence of phosphorus and the results were compared with MAI prepared using methods known in the art as well as commercially available MAI. The results are summarized in Table 1.
[0120] Example II - Synthesis of Octylammonium Iodide (OAI) without Catalyst:
[0121] A portion of iodine (I2) was dissolved in ethanol in a round-bottom flask in a single step to obtain a non-translucent dark brown solution, demonstrating the presence of molecular iodine (I2). After 15 minutes, the iodine dissolved in the ethanol and the solution remained dark brown and opaque. Formic acid was then added to the flask in a HCOOH:I2 molar ratio of 0.97:1.0, and no changes were observed in the flask. 2.6 moles of octylamine per mole of I2 iodine were then slowly added dropwise to the solution. After each drop of octylamine was added, bubbles and foam appeared in the reaction solution, and the temperature of the reaction mixture was observed to increase due to its exothermic process. The bubbles and foam indicate that the octylamine reacted with the hydrogen iodide HI generated in situ. After all the octylamine was added (the reaction mixture remained brown), the flask was heated for 2 hours while the temperature of the reaction mixture was maintained at 80°C. The reaction was then terminated and the resulting mixture was light brown, however, since an excess of iodine (I2) was used, the color of the mixture was not considered an indicator of the termination of the reaction, which prevented its complete reaction. An excess of iodine relative to formic acid was used prevent The formation of octylamine formate (which will be a by-product of the synthesis) and thus prevent The obtained octyl ammonium iodide (OAI) is contaminated. When the reaction is finished, the solution is kept in a flask and the mixture is evaporated on a rotary evaporator under a reduced pressure of 30 mbar. During the evaporation, in a water bath at a temperature of 50°C, the evaporation gives a yellow and brown powder, which is then dissolved in boiling anhydrous ethanol and recrystallized in 1 mL of anhydrous ethanol per 1 g of the expected product (assuming a yield of 1 mL / 1 g). The solution is then cooled and ether is added to the cooled mixture to increase the precipitation efficiency. A white precipitate is obtained by filtration and washed with ether until the precipitate becomes white. The resulting precipitate constituting the reaction product (OAI) is vacuum dried (pressure less than 0.2 mbar) for 5 hours and the product is then weighed. A 76% yield of the product (OAI) is obtained compared to the theoretical yield according to the stoichiometry of the reaction.
[0122] Example III - Synthesis of Formamidine Iodide (FAI) without Catalyst:
[0123] A portion of iodine (I2) was dissolved in ethanol in a round bottom flask in a single step to obtain a non-translucent dark brown solution, proving the presence of molecular iodine (I2). After 15 minutes, the iodine dissolved in the ethanol and the solution remained dark brown and opaque. Then 1.0 Eq (equivalent) of formic acid HCOOH (relative to iodine (I2)) was added to the flask, and no changes were observed in the flask. Then acetic acid formamidine (solid at room temperature) was added to the solution in a single step with a total amount of 2.1 Eq (equivalent) of acetic acid formamidine (relative to iodine (I2)). After the addition of acetic acid formamidine (the reaction mixture remained brown), the flask was heated for 12 hours, and the reaction mixture temperature was maintained at 50°C. The reaction was then terminated and the resulting mixture was light brown. When the reaction was completed, the mixture was evaporated on a rotary evaporator under a reduced pressure of 30 mbar, and the flask containing the solution was maintained in a 50°C water bath for evaporation, and the evaporation gave a yellow and brown powder. Then it is dissolved in boiling absolute ethanol, recrystallized in 1mL absolute ethanol of every 1g expected product (assuming a yield of 1mL / 1g). Then the solution is cooled and ether is added to the cooled mixture to improve the precipitation efficiency. Filter to obtain a white precipitate, wash with ether until the precipitate becomes white. The resulting precipitate forming the reaction product (FAI) is vacuum dried (pressure is less than 0.2 millibar) for 5 hours, and the product is then weighed. Compared with the theoretical yield according to the stoichiometric reaction, 82% product (FAI) yield is obtained.
[0124] The resulting products were also tested for the presence of phosphorus. The results are summarized in Table I below.
[0125] Table 1:
[0126]
[0127] Example IV - Preparation of a perovskite-forming composition in ink form using MAI as a perovskite precursor:
[0128] The perovskite-forming composition was prepared by dissolving the following compounds in 954 μL dimethylformamide (DMF):
[0129] - 305.14 mg of methylammonium iodide (MAI) prepared according to the procedure of Example 1 above,
[0130] -166.50mg anhydrous lead (II) acetate Pb(CH3COO)2,
[0131] -35.58 mg Lead(II) chloride PbCl2
[0132] - a solution of methylammonium dihydrogen(I) phosphate (CH3NH3H2PO2) in DMF at a concentration of 19.8 mg / mL in an amount of 46 μL (corresponding to 0.3 wt% CH3NH3H2PO2 based on the MAI used).
[0133] The ingredients were mixed for 12 hours and then the resulting colloidal solution was filtered using a 0.45 μM filter to obtain a colloid with a suitable dispersed phase particle size.
[0134] The obtained composition has a stable colloidal form suitable for printing (ink). No change in the colloidal particle size and no tendency to aggregation are observed. During the observation period of several weeks, the composition remains in the form of a clear (translucent) colloidal solution.
[0135] The obtained colloid (containing single crystal MAI) is as follows Fig.14A As shown in the pictures I, II, III, and IV in the figure, the pictures show the same colloid sample, where picture I shows the sample on the day of colloid preparation, picture II is the colloid 24 hours after preparation, picture III is the colloid 96 hours after preparation, and picture IV is the colloid 168 hours after preparation, confirming that the clarity of the colloid has not changed over time. For comparison, Fig. 14B , 14C and 14D show images of colloids with the same composition, Fig. 14B Pictures showing colloids containing conventionally prepared commercially available MAI (without using in situ generated HI); Fig. 14C Shown are colloids containing MAI prepared using methods known in the art, a colloid containing single recrystallized MAI, and Fig.14D Shown are colloids with MAI obtained by methods known in the art, a colloid containing thrice-recrystallized MAI. Fig. 14B and Fig.14A Similarly, the following photos are shown: I, II, III and IV of the same colloid sample, respectively, where I was taken on the day of its preparation, II was taken 24 hours after preparation, III was taken 96 hours after preparation and IV was taken 168 hours after preparation, Fig. 14C I shows the colloid picture taken on the day of preparation. Fig. 14C II shows a colloid picture taken 72 hours after the preparation of the colloid. Similarly, Fig.14D I shows the pictures of the colloid preparation on the day, Fig.14D II shows a picture taken 72 hours after the preparation of the colloid, and Fig.14D III shows a picture taken 144 hours after the preparation of the colloid, which illustrates the change in transparency of the MAI-containing colloid prepared using a method known in the art over time. This is due to Fig. 14B and 14C It should be noted that the colloid prepared with MAI recrystallized only three times had no visible (visible to the naked eye) turbidity after 144 hours, and no such turbidity was observed in the colloid prepared with MAI of the present invention, but a single recrystallization was performed. This further demonstrates the excellent parameters of the iodide (MAI) prepared using the method of the present invention.
[0136] Fig.14A , 14B All the photos in 14C and 14D were taken under the same lighting conditions by shining a flashlight on the colloid to show the Tyndall effect. Therefore, the studies conducted confirmed the improved stability ( Fig.14A ) and an overall improved clarity of the colloid.
[0137] Therefore, the perovskite-forming composition prepared in the form of a colloidal solution contains the MAI of the present invention as one of the perovskite-forming components.
[0138] Example V - Preparation of perovskite coating using MAI:
[0139] Three perovskite-forming compositions were prepared as follows:
[0140] - Composition I, comprising the same ingredients as the perovskite-forming composition of Example IV above, using MAI obtained by a method known in the art
[0141] - Composition II, comprising the same components as the perovskite-forming composition of Example IV above, but without the addition of CH3NH3H2PO2,
[0142] - Composition III, comprising the same ingredients as the perovskite-forming composition of Example IV above, wherein the MAI used is MAI obtained by the method according to the present disclosure with the addition of CH3NH3H2PO2).
[0143] Next, the substrates for applying compositions I, II and III were prepared as follows: the sheets were cut from PET / ITO (ethylene terephthalate / indium tin oxide) sheets by a laboratory punch, and then the desired pattern was obtained in the ITO conductive layer by etching in a 15% hydrochloric acid (HCl) solution by soaking. The etched sheets were cleaned in an ultrasonic bath (cleaning solutions used: deionized water, isopropyl alcohol). The substrates thus prepared were air-dried at 95° C. for 1 hour, and then PEDOT:PSS (poly(3,4-ethylene-1,4-dioxyethiophene:styrene polysulfonate) was applied to the cleaned and dried substrates using a spin coating method in air. The substrates were then heated at 95° C. in air for 45 minutes. The respective perovskite-forming compositions (composition I, composition II, composition III) were then applied to the corresponding sheets using a spin coating technique in a nitrogen atmosphere. In order to crystallize the perovskite material, the substrates coated with the films of the respective perovskite-forming compositions (composition I, composition II, composition III) were heated at 96° C. for 15 minutes.
[0144] The resulting perovskite coating in the form of a thin film on a PEDOT / PET / ITO substrate was then observed under a scanning electron microscope (SEM) and photographed as follows: Fig. 7A , Figure 7B and Figure 7C The picture shown, Fig. 7A is a SEM image of a perovskite coating prepared using composition I, wherein the composition contains MAI prepared using methods known in the art , Figure 7B is a SEM picture of a perovskite coating prepared using composition II, wherein the composition contains MAI prepared using the method according to the present disclosure, But not adding Add CH3NH3H2PO2 ,and Figure 7C is a SEM photograph of a perovskite coating prepared using composition III, wherein the composition comprises make use According to the present disclosure Methods for preparation of MAI , and CH was added 3NH3H2PO2 .
[0145] The results of SEM analysis of the perovskite coatings prepared with compositions I, II, and III demonstrate the improved morphology of the perovskite coatings prepared with MAI obtained using the method according to the present disclosure.
[0146] like Fig. 7A As shown in the photographs in , the perovskite layer (with prior art MAI) is dense, i.e. it does not contain any pinholes, and is characterized by small grains of perovskite material.
[0147] Prepared using MAI obtained according to the method of the present disclosure Figure 7B The perovskite layer is characterized by larger grains and improved crystallinity, which is more beneficial for the operation of the battery; in addition, pinholes can be seen in the layer.
[0148] Now, using MAI prepared Figure 7C The layer obtained by the method according to the present disclosure and with the addition of CH3NH3H2PO2 is characterized by also having larger grains and, moreover, a reduced number of pinholes. This can be achieved by adding CH3NH3H2PO2 in an amount of 0.3 wt. % CH3NH3H2PO2 relative to the weight of MAI, which allows adjusting the chemical parameters of the perovskite-forming composition as a colloidal solution to obtain an optimized morphology of the perovskite layer.
[0149] The obtained coating was also analyzed using X-ray diffraction test, and the diffraction pattern obtained was as follows Fig. 8A , Figure 8B and Figure 8C As shown, Fig. 8A Diffraction showing the CH3NH3PbI3 perovskite network, Figure 8BThe enlarged peak corresponding to the reflection (110) in the tetragonal plane of the perovskite phase is shown, while Figure 8C The amplified (control) peak corresponding to the PET material is shown, with negligible differences between samples.
[0150] For all coatings obtained using compositions I, II and III, the thickness measured using an optical profilometer was the same, so the differences in the peak intensities in the diffraction patterns were not due to the different amounts of perovskite material between the samples. The obtained X-ray diffraction patterns showed that for the samples with MAI prepared according to the present disclosure (compositions II and III), the peak intensities corresponding to the positions of the perovskite reflections were higher, especially the peak at 14° corresponding to the reflection (110) in the tetragonal symmetry of the perovskite material ( Figure 8B ). This is due to the formation of a higher proportion of crystalline phases and / or a higher level of perovskite grain orientation, which is particularly advantageous for photoactive perovskite coatings for photovoltaic applications and can provide improved functionality when used in solar cells.
[0151] Example VI - Preparation of perovskite photovoltaic cells using MAI:
[0152] To produce a photovoltaic cell having a photosensitive perovskite layer, a perovskite composition was prepared using the composition described in Example V above, namely:
[0153] - Composition I, comprising the ingredients of the perovskite-forming composition of Example IV above, using MAI obtained by methods known in the art,
[0154] - Composition II, comprising the ingredients of the perovskite-forming composition as described above in Example IV, including MAI according to the present disclosure (with in-situ generated HI) but without the addition of CH3NH3H2PO2,
[0155] - Composition III, comprising the ingredients of the perovskite-forming composition as described in Example IV above, wherein the MAI used is the MAI obtained by the method according to the present disclosure, and CH3NH3H2PO2 is added).
[0156] The above composition was used to prepare a photovoltaic cell with a simple sandwich structure comprising the following layers: PET / ITO / PEDOT:PSS / Perovskite:CH3NH3PbI3 / PCBM / BCP / Ag.
[0157] For this purpose, substrates comprising layers of PET / ITO / PEDOT:PSS / perovskite:CH3NH3PbI3 were prepared for each cell using the above-mentioned perovskite-forming compositions I, II and III.
[0158] After obtaining the perovskite layer, a PCBM (phenyl-C61-butyric acid methyl ester) solution dissolved in anhydrous chlorobenzene at a concentration of 20 mg / mL was immediately deposited on the perovskite layer of each cell using a spin coating method under nitrogen (inside a glove box). For each cell, the deposited PCBM layer was heated at 60°C for 10 minutes.
[0159] Then on 1.10 -6 A 5 nm BPC (bathocuproine) layer and a 90 nm silver (Ag) layer were thermally vapor deposited sequentially at a predetermined pressure of 100 mbar.
[0160] The characteristics of the obtained battery are as follows Fig. 9A As shown, the measurement results of the cell efficiency (η) are presented, which determines the energy conversion efficiency of the cell, depending on the type of perovskite-forming compositions I, II and II used for the perovskite layer of the cell. The measurement results confirm the improvement of the efficiency of the cell with the perovskite layer of the perovskite composition II, which has the MAI of the present invention, and show a further significant improvement in the efficiency of the cell with the perovskite layer of the composition III, which has the MAI of the present invention and the added CH3NH3H2PO2, compared to the cell containing the perovskite layer of the composition I with the MAI of the prior art.
[0161] on the other hand, Fig. 9B is a summary of the test results showing the current density-voltage correlation, which also confirms the improved parameters of cells with perovskite layers made of compositions II and III containing MAI obtained according to the method disclosed herein. Fig. 9B As shown in the graph, the average efficiency of the cell with the perovskite layer of composition II is 8.2%, while the efficiency of the cell with the perovskite layer of prior art composition I ranges from 7.2 to 8.0%, which indicates that the cell efficiency has been improved by 2.5% to 14%. The cell with the perovskite layer made of composition III (comprising MAI and CH3NH3H2PO2 according to the present disclosure) shows an additional efficiency increase relative to both the cell of composition I and the cell of composition II. The efficiency of the cell of composition III ranges from 9.0 to 9.2%.
[0162] Furthermore, it was found during the work that cells having perovskite layers made of compositions II and III exhibited improved reproducibility and long-term operational stability compared to cells having a perovskite layer made of composition I comprising prior art MAI, which was due to the differences in defect density of the perovskite layers made of the respective compositions I, II, III.
[0163] In addition, selected cells were subjected to aging tests: the cells were heated at 800 W / m 2The results of these tests are summarized in Fig.10 In the present invention, it is shown that cells containing perovskite layers with the MAI of the present invention show good performance over an extended period of time. In particular, the use of the MAI obtained according to the present disclosure enables better control of the quality of the perovskite layer obtained, including in particular a greater crystallinity of the perovskite layer, which can lead to improved stability of cells produced with such perovskites.
[0164] Example VII - Preparation of a Perovskite-Forming Composition Using FAI:
[0165] The perovskite-forming composition was prepared by dissolving the following compounds in a mixture of 400 μL dimethylformamide (DMF) and 100 μL dimethyl sulfoxide (DMSO):
[0166] - 95.01 mg of formamidine iodide (FAI) prepared according to the procedure of Example III above,
[0167] -38.53 mg methylammonium bromide CH3NH3Br,
[0168] -274mg lead (II) iodide PbI2
[0169] -Cesium iodide (CsI) solution in toluene, concentration 2M.
[0170] The ingredients were mixed for 12 hours and then the resulting colloidal solution was filtered using a 0.45 μM filter to obtain a colloid with a suitable dispersed phase particle size.
[0171] The composition obtained has the form of a stable colloid. No changes in the size of the colloid particles are observed, nor is there a tendency to agglomeration (as is the case with colloids containing prior art FAI). During several weeks of observation, the composition is in the form of a transparent (translucent) colloidal solution.
[0172] Therefore, the perovskite-forming composition prepared in the form of a colloidal solution contains the FAI of the present invention as one of the components (perovskite precursor) for forming perovskite.
[0173] Example VIII - Preparation of Perovskite Coating Using FAI:
[0174] Two perovskite-forming compositions were prepared as follows:
[0175] - Composition I, comprising the same ingredients as the perovskite-forming composition of Example VII above, but using FAI obtained by a method known in the art,
[0176] - Composition II, containing the same ingredients as the perovskite-forming composition of Example VII above, but containing FAI prepared by the method according to the present disclosure.
[0177] The substrate for deposition of compositions I and II was then prepared as described in Example V above. A layer of PTAA in toluene was then applied to the plate by spin coating a PTAA (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]) solution in toluene (concentration 2 mg / mL, solution filtered using a 0.2 μm filter). Composition I (control) and composition II were applied to the substrate separately using a spin coating technique under nitrogen with the following predetermined parameters: spin time: 30 seconds, acceleration: 2500 rpm, spin speed: 2500 rpm. At the last 8 seconds of the coating, ethyl acetate (as anti-solvent) in an amount of 1000 μL per plate was added dropwise to the film being prepared. The film was then heated at 100°C for 40 minutes to obtain the perovskite structure.
[0178] The resulting perovskite coating in the form of a thin film on the substrate was then observed under a scanning electron microscope (SEM), and pictures such as Fig.11A and Fig. 11B As shown, Fig.11A is a SEM image of a perovskite coating prepared using composition I, wherein composition I contains FAI prepared using methods known in the art ,and Fig. 11B is a SEM picture of a perovskite coating prepared using composition II, which contains FAI prepared using the method according to the present disclosure.
[0179] The results of SEM analysis of the perovskite coatings prepared with compositions I and II confirm the good morphology of the perovskite coatings prepared with the FAI obtained using the developed method. The images show larger grains of the perovskite material obtained from the FAI of the present invention compared to the perovskite prepared with the prior art FAI.
[0180] The obtained coating was also analyzed using X-ray diffraction test, and the diffraction pattern obtained was as follows Fig. 12A and Fig. 12B As shown, Fig. 12A Diffraction showing the obtained perovskite network: Cs 0,1 (FA 0,83 MA 0,17 ) 0,9 Pb(I 0,84 Br 0,16 )3, wherein MA is a methylammonium moiety and FA is a formamidine moiety; Fig. 12B A zoomed-in peak of reflection (100) corresponding to the cubic perovskite phase is shown.
[0181] For all coatings obtained using compositions I and II, the thickness measured using an optical profilometer was the same, so the differences in peak intensity in the diffraction patterns were not caused by different amounts of different perovskite materials between the samples. The obtained X-ray diffraction patterns show that for the sample with FAI according to the present disclosure (composition II), the peak intensity corresponding to the perovskite reflection position is higher, especially the (100) ( Fig. 9B ). This is due to the formation of a higher share of crystalline phases and / or a higher level of perovskite grain orientation, which is particularly advantageous for photoactive perovskite coatings for optoelectronic applications.
[0182] Example IX - Preparation of perovskite photovoltaic cells using FAI:
[0183] To produce a photovoltaic cell with a perovskite photoactive layer, a perovskite composition was prepared using the ingredients as in Example VIII above, comprising FAI according to the present disclosure (Composition II with HI prepared in situ).
[0184] The above composition is used to prepare a photovoltaic cell having a simple sandwich structure comprising the following layers: PET / ITO / PTAA / Perovskite: Cs 0,1 (FA 0,83 MA 0,17 ) 0,9 Pb(I 0,84 Br 0,16 )3 / PCBM / BCP / Ag.
[0185] For this purpose, a PET / ITO / PTAA / perovskite:Cs 0,1 (FA 0,83 MA 0,17 ) 0,9 Pb(I 0,84 Br 0,16 )3 is a base material for each layer.
[0186] The PCBM, BCP and Ag layers were then applied separately using the same method as in Example VI above.
Claims
1. A method for obtaining a compound having the general formula R x A method for preparing a salt of NI, wherein R x N is an organic cation R x N + , R represents a substituent R-, independently selected from an organic substituent R 1 -、R 2 -、R 3 - and hydrogen H-, and an organic cation R x N + The donor comprises independently selected from the group consisting of y H z As part of the organic substituent R 1 -、R 2 - and optionally R 3 -, and the alkyl substituent contains 1 to 8 carbon atoms in the substituent molecule, and optionally contains at least one heteroatom replacing a carbon atom or a hydrogen atom in the substituent molecule, wherein the heteroatom is selected from the group consisting of oxygen, nitrogen, sulfur, iodine, chlorine and bromine, x is the organic cation RxN + The number of substituents R- directly attached to the nitrogen atom N in, where x is 3 or 4, I is the iodide anion I - , Characterized in that the method is an in-situ process and comprises preparing a reaction mixture and maintaining the reaction mixture at a temperature not less than 20° C. for a desired time to obtain a compound having the general formula R x The reaction product of NI salt, The following steps are included in the preparation of the reaction mixture: The catalyst is introduced into the solvent medium, wherein the catalyst has the general formula R x NI of salt, In a solvent medium, hydrogen iodide HI is synthesized by mixing molecular iodine I2 with formic acid HCOOH in a molar ratio of molecular iodine I2: formic acid HCOOH of 1.01:1 to 2.0:1, To provide organic cation R x N + The amount of donor: molecular iodine I2 in a molar ratio of not less than 1.01:1 will serve as the organic cation R x N + introducing a donor compound into the solvent medium; Among them, amine is used as the organic cation R x N + donor, and the obtained salt R x NI comprises an organic cation R selected from the group consisting of x N + :Alkyl ammonium cation R(H3)N + , dialkylammonium cation R2(H2)N + and trialkylammonium cation R3(H)N + ; Alternatively, wherein formamidine acetate is used as the organic cation R x N + Donor, used to obtain formamidine iodide FAI, namely H2N-C(H)=N(H2)I.
2. The method according to claim 1, wherein: Molecular iodine I2 and formic acid HCOOH are mixed in a molar ratio of molecular iodine I2: formic acid HCOOH of 1.01:1 to 1.1:1, And, to provide an organic cation R x N + The molar ratio of donor: molecular iodine I2 is 1.01:1 to 1.50:
1. x N + A donor is introduced into the solvent medium, After the synthesis of hydrogen iodide HI, the organic cation R x N + The donor is introduced into a solvent medium and the prepared reaction mixture is heated to a temperature in the range of 20 to 80°C.
3. The method according to claim 1 or 2, wherein: The organic cation R used x N + The donor is selected from the group consisting of methylamine for obtaining methylammonium iodide MAI or octylamine for obtaining octylammonium iodide OAI.
4. The method according to claim 1 or 2, wherein: The solvent medium comprises at least one selected from the group consisting of methanol, ethanol, anhydrous ethanol, isopropanol, di a compound of the group consisting of alkanes, tetrahydrofuran (THF) and dimethylformamide (DMF), or water.
5. The method according to claim 1, wherein: The catalyst is obtained by the process according to any one of claims 1 to 4.
6. The method according to any one of claims 1 or 5, wherein: The catalyst is introduced in a catalyst:molecular iodine I2 molar ratio ranging from 0.01:1 to 0.03:1.
Citation Information
Patent Citations
Ink compositions for photovoltaics
US20130087744A1
A film-forming compostion and a method for manufacturnig a photoactive film
WO2016088019A1
Optoelectronic devices with organometal perovskites with mixed anions
CN104662625A
Method for producing hydroiodic acid and method for producing aqueous metal iodide solution
JP6330064B1